2020
DOI: 10.3390/ijms21176213
|View full text |Cite
|
Sign up to set email alerts
|

GM2 Gangliosidoses: Clinical Features, Pathophysiological Aspects, and Current Therapies

Abstract: GM2 gangliosidoses are a group of pathologies characterized by GM2 ganglioside accumulation into the lysosome due to mutations on the genes encoding for the β-hexosaminidases subunits or the GM2 activator protein. Three GM2 gangliosidoses have been described: Tay–Sachs disease, Sandhoff disease, and the AB variant. Central nervous system dysfunction is the main characteristic of GM2 gangliosidoses patients that include neurodevelopment alterations, neuroinflammation, and neuronal apoptosis. Currently, there is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 180 publications
0
67
0
1
Order By: Relevance
“…GM2 gangliosidoses include the Tay-Sachs disease, the Sandhoff disease, and the GM2 AB, which result from LoF mutations in the genes HEXA, HEXB, and GM2A, respectively (Dastsooz et al, 2018). These variants of GM2 gangliosidoses are clinically indistinguishable, but are all associated with betahexosaminidase deficiency (Leal et al, 2020). All three variants are usually fatal by early childhood.…”
Section: Gm2 Gangliosidosesmentioning
confidence: 99%
“…GM2 gangliosidoses include the Tay-Sachs disease, the Sandhoff disease, and the GM2 AB, which result from LoF mutations in the genes HEXA, HEXB, and GM2A, respectively (Dastsooz et al, 2018). These variants of GM2 gangliosidoses are clinically indistinguishable, but are all associated with betahexosaminidase deficiency (Leal et al, 2020). All three variants are usually fatal by early childhood.…”
Section: Gm2 Gangliosidosesmentioning
confidence: 99%
“…Patients with Sandhoff disease may also exhibit prominent dysautonomic features, including urine incontinence or constipation, especially those with adult-onset disease [52][53][54][55].…”
Section: Lower Motor Neuron Diseasementioning
confidence: 99%
“…Since GM2 ganglioside buildup promotes the accumulation of others lipids such as phospholipids, cerebrosides, sphingomyelin, and cholesterol (Leal, Benincore-Florez, et al, 2020), the staining of these lipids could be used as an assay for drug development. In this sense, it was reported that Nile Red staining offers a valid method for evaluating drug efficacy and compound screening in TSD patient neural stem cells (Vu et al, 2018).…”
Section: Ganglioside and Lysosomal Mass Reductionmentioning
confidence: 99%
“…Currently, the treatment of GM2 gangliosidoses is mainly focused on palliative interventions, and in the delay of disease progression in the late-onset form. However, several therapy approaches for TSD or SD are under development including enzyme replacement therapy (ERT), bone marrow or neural progenitor cell transplantation, gene therapy, and substrate reduction therapy (Leal, Benincore-Florez, et al, 2020;Solovyeva et al, 2018). Nowadays, ERT is available for 11 LSDs treatment including Gaucher, Fabry, Pompe, neuronal ceroid lipofuscinoses type II, α-mannosidosis, acid lipase deficiency, and mucopolysaccharidoses type I, II, IVA, VI, and VII .…”
mentioning
confidence: 99%
See 1 more Smart Citation